2003
DOI: 10.1149/1.1566964
|View full text |Cite
|
Sign up to set email alerts
|

Concentration Quenching of Photoluminescence

Abstract: The relative emission efficiency of F 3 ϩ and F 2 centers as a function of their concentration has been investigated in LiF crystals colored at room temperature and Ϫ60°C with 3 MeV electrons. From a careful study of their absorption and emission spectra, we discovered that the emission efficiency of both F 3 ϩ and F 2 defects is constant up to ϳ10 16 centers/cm 3 . When increasing the concentration up to 10 18 centers/cm 3 , decreases slightly for the F 2 centers and considerably for the F 3 ϩ ones, a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…11, at the highest dose the primary F centers reach an average density of 5 × 10 19 centers cm −3 and the F 2 one is estimated ∼10 18 centers cm −3 , with respect to 6.1 × 10 22 halogen sites cm −3 in LiF. At this high CCs densities, also quenching phenomena will differently affect the PL of F 2 and F 3 + defects, 79 especially for the F 3 + ones. 80 According to Fig.…”
Section: Lif Imaging Detectors Based On Rpl For Advanced Proton Beam ...mentioning
confidence: 90%
“…11, at the highest dose the primary F centers reach an average density of 5 × 10 19 centers cm −3 and the F 2 one is estimated ∼10 18 centers cm −3 , with respect to 6.1 × 10 22 halogen sites cm −3 in LiF. At this high CCs densities, also quenching phenomena will differently affect the PL of F 2 and F 3 + defects, 79 especially for the F 3 + ones. 80 According to Fig.…”
Section: Lif Imaging Detectors Based On Rpl For Advanced Proton Beam ...mentioning
confidence: 90%
“…These results suggested that the contribution of DCJTB to EL spectrum of device is bigger in the doped device than in the undoped device. Considering that DCJTB concentration is higher in the undoped device, the smaller contribution of DCJTB obviously originates from concentration quench effect (CQE) of DCJTB, which is a common sense in dye-doped device as widely reported in literatures [9,10]: as concentration of the fluorescent dye increases, excitons concentration of the dye also increases. As a result a stronger interaction between excitons will appear, leading to more excitons deactivate nonradiatively or, in other words, more serious exciton-exciton quenching.…”
Section: Methodsmentioning
confidence: 96%